Hubungan Layanan Kesehatan Gigi Dan Mulut Dengan Tingkat Kepuasan Pasien di RSGM Prima Medan Tahun 2024 - Nurhasanah, Fadillah; Suryani, Linda; Wirza, Wirza; Wilis, Ratna (NASUWAKES: Jurnal Kesehatan Ilmiah, 2025)
Patient satisfaction is achieved when patients receive services that are in accordance with their desires, needs and expectations. This study aims to determine the relationship between dental and oral health services and the level of patient satisfaction at RSGM Prima Medan in 2024. This research was carried out using analytical methods with a cross sectional design with the chi square test. The research was carried out on March 8-28 2024 with a sample size of 44 people by completing a questionnaire by patients to determine dental and oral health services and the level of patient satisfaction.The research results showed that dental and oral health services were in the good category for 37 (84.1%) respondents. And patient satisfaction was Pin the satisfied category as many as 35 (79.5%) respondents. Based on the research results, the value of ρ valeu = 0.002 < α 0.05. It can be concluded that there is a relationship between dental and oral health services and the level of patient satisfaction at RSGM Prima Medan. It is recommended that RSGM Prima Medan staff maintain the quality of dental and oral health services and conduct health service surveys on patient satisfaction periodically in an effort to improve the quality of health services.